The In silico Study: Curcumin Potential As A Topoisomerase Enzyme Inhibitor in The Replication Process of Plasmodium Falciparum That Causes Cerebral Malaria - Any Fira Safitri; Risma Risma; Olivia Mahardani Adam; Danny W. Danandjaja (Eduvest - Journal of Universal Studies, 2025)
Turmeric (Curcuma longa) contains the active compound curcumin, which has antiprotozoal, antimalarial, anti-inflammatory effects. This study aims to ignite the potential of curcumin, which has the potential as an antiprotozoal through inhibition of Plasmodium Falciparim replication through the topoisomerase enzyme. The method used in this study is the One Shot Experimental Study, with several stages including preparation of active compounds, prediction of active substance binding energy, prediction of compound binding, molecular docking, prediction of ADME (absorption, distribution, metabolism, excretion) and toxicity. The results show that curcumin binds to the same site as Artemisinin, both also interact with the topoisomerase VI protein and provide similar inhibitory effects. ADME predictions show that curcumin has good potential for use as an oral drug, with both LD50s included in class 4. The binding affinity and bioactivity of curcumin are lower than Artemisinin but are still considered to have the potential as a safer antiprotozoal alternative.